2018
DOI: 10.5530/ijper.52.4s.108
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a LC-ESI-MS/MS Based Bioanalytical Method for Dapagliflozin and Saxagliptin in Human Plasma

Abstract: Objective: To develop a new, rapid and sensitive LC-ESI-MS/MS method for the simultaneous estimation of Dapagliflozin and saxagliptin in human K 2 EDTA plasma by Liquid-liquid Extraction method (LLE) using deutereated dapagliflozin (DGd2) and saxagliptin (SGd5). Method: Chromatographic separation was carried out on a reverse phase hypersil Gold C 18 (50mmx3.0mm, 5µm) column using mixture of 10 mM Ammonium acetate and methanol (20:80, v/v) at a flow rate of 0.5ml/min in isocratic mode. Quantification was achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The polynomial equation revealing percent extraction recovery, R1 for MET was +70. Validation of bioanalytical method was carried out [25] . For both the drugs, linearity was obtained in the range of 0.022-2.2 μg/ml for MET and 0.0012-0.12 μg/ml for ALO with correlation coefficient of 0.9907 and 0.9918 respectively (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The polynomial equation revealing percent extraction recovery, R1 for MET was +70. Validation of bioanalytical method was carried out [25] . For both the drugs, linearity was obtained in the range of 0.022-2.2 μg/ml for MET and 0.0012-0.12 μg/ml for ALO with correlation coefficient of 0.9907 and 0.9918 respectively (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Literature review shows minimal methods has been developed and reported for Dapagliflozin estimation by HPLC as an individual drug [3,[17][18][19][20] and in combination with Saxagliptin and Metformin [21][22][23][24] where the reported methods has vary retention time, high run time and more consumption of organic solvents for the estimation. This study focused on developing an RP-HPLC method of Dapagliflozin which is more economical, new, rapid, precise and accurate with a good amount of separation, consuming less organic solvents for separation as compared to the reported research work mentioned above.…”
Section: Fig 1: Chemical Structure Of Dapagliflozinmentioning
confidence: 99%
“…Now a day, stability indicating method as important regulatory and CGMP point of view to assess the drug stability. In the present study, it was tired to develop stability indicating RP-HPLC method to determine possible degradation products of DAPA and MET [18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%